Evapotranspiration and Inputs of Salts to Soil in Irrigated Millet with Wastewater - Silva, José Raliuson Inácio; de Mello Vieira Leite, Mauricio Luiz; Barros, Genival; de Sousa Silva, Josefa Edinete; da Silva, Elania Freire; da Rosa Ferraz Jardim, Alexandre Maniçoba [UNESP]; Neto, Juracy Barroso; de Sousa Lima, José Romualdo; Antonino, Antônio Celso Dantas; Souza, Eduardo (MDPI, 2025)
The growing reliance on unconventional water sources requires effective strategies for forage production, particularly in semiarid regions. The objective of this study was to evaluate evapotranspiration, phytomass accumulation, and salt inputs to the soil in millet crops irrigated with wastewater under different soil water levels, both with and without organic fertilizer. We conducted the experiment in a protected environment using a randomized block design in a 4 × 2 + 1 (control) factorial scheme with three replicates. We applied four irrigation levels with wastewater (25, 50, 75, and 100% of available soil water) with or without organic fertilizer. The control treatment was watering with the public supply submitted to 100% of the available water from the soil without fertilization. Wastewater did not affect biomass without fertilization, but irrigation levels significantly influenced productivity under fertilization. Additionally, applying 50% of available soil water proved the most efficient system in terms of yield per unit of water consumed. Although irrigation improved productivity, water use efficiency in millet showed limited enhancement. The millet did not exhibit any symptoms of salt stress. Finally, we emphasize caution when using wastewater (graywater) for irrigation, as continuous application can lead to salt accumulation and subsequent soil salinization.